Research on Impact of Female College Students’ Beauty Consumption on Industry Marketing Strategies - Xi Zixuan (SHS Web of Conferences)
This study examines the significant influence of female college students’ beauty consumption behavior on the marketing strategies within the beauty industry. Recognizing the pivotal role this demographic plays in shaping beauty trends and driving market dynamics, the research delves into how brands can effectively engage with this influential group. Through case studies of successful brands like Fenty Beauty and Glossier, the paper illustrates the power of inclusivity, authenticity, and community-driven marketing in building strong brand loyalty and enhancing consumer engagement. The study also identifies key challenges that beauty brands face, such as the necessity of staying attuned to rapidly evolving trends and the potential pitfalls of an over-reliance on digital marketing channels. To address these challenges, the research proposes strategic approaches, including cultivating authenticity through meaningful influencer partnerships, innovating product offerings based on deep consumer insights, and striking a balance between digital and experiential marketing efforts. Ultimately, this study underscores the business value of adapting marketing strategies to the evolving preferences of female college students, offering practical guidance for brands seeking to strengthen their market relevance and maintain a competitive edge in the dynamic beauty industry.